Straight Baselines in International Maritime Boundary Delimitation - Reisman, W. Michael. author. aut Link
XVI, 242 p.
Keywords: The practice of extending the boundary of the sea or baseline has removed sections of the ocean from international use. This book examines the genesis of the straight baseline in international law and the forces that exploited it as a technique of maritime expansion not boundary delimitation.